The Effect Of Dosing Potash Fertilizer And Compost Doses Of Empty Bunches Of Oil Palm (Tkks) On The Growth Of Citronella Plants (Cymbopogon Nardus L.) - Abdul Hasyim Sodiq; Karina Dieta Sheren; Andi Apriany Fatmawaty; Susiyanti Susiyanti (Department of Crop Science, Faculty of Agriculture, Andalas University, 2023)
Citronella is a biopharmaceutical plant that has the main content of citronella and geraniol as raw materials in the manufacture of essential oils (citronella oil) which have high economic value. The production of citronella increases every year although the amount is still small when compared to the production of other biopharmaceutical plants. So it is necessary to increase the productivity of citronella plants with the use of the right dose of fertilizer. This study aims to determine the effect of potassium fertilizer dose and Compost Dose of Empty Palm Oil Bunches (EFB) on the growth of citronella (Cymbopogon nardus L.). The research was started in February-June 2022 at Balai Pengkajian Teknologi Pertanian (BPTP) Banten, Ciruas District, Serang Regency, Banten and the Laboratory of the Department of Agroecotechnology, Faculty of Agriculture, Sultan Ageng Tirtayasa University. This study used a Randomized Block Design (RBD) method which consisted of two factors, namely potassium fertilizer dose and Compost Dose of Empty Palm Oil Bunches (EFB). The first factor has 4 levels, 0 kg/ha potassium (K0), 15 kg/ha (K1), 30 kg/ha (K2) and 45 kg/ha (K3). The second factor has 4 levels, 0 tons/ha (T0), 20 tons/ha (T1), 30 tons/ha (T2) and 40 tons/ha (T3). There were 16 treatment combinations with 3 replications so 48 experimental units were obtained. Each experimental unit contained 2 polybags where each polybag contained 2 plants, so the total plants in the study were 192 plants. The results showed that the dose of potassium fertilizer 30 kg/ha gave the best results on plant height parameters at the age of 3, 4, 5, 6 WAP, the dose of potassium fertilizer 15 kg/ha gave the best results on the number of leaves aged 1 WAP. Dosage of 40 tons/ha of TKKS compost gave the best results on the number of leaves aged 5 and 6 WAP. There was no interaction between the dose of potassium fertilizer and the dose of TKKS compost on all parameters at the age of 1-12 WAP